EFFECTIVE INTEGRATION OF LEARNING MANAGEMENT SYSTEM INTO TERTIARY EDUCATION (Conferencea, 2023)
Nowadays, higher education is being intensely influenced by modern educational changes, the advent of the knowledge society, societal alterations, as well as globalization which resulted in quality of education introducing online learning or more precisely, technologically enhanced learning. The presented overview of this paper points towards how to effectively integrate Learning Management System into tertiary education in order to achieve successful outcome in learning and its role both in teaching and learning processes. Through LMS teachers can teach their students meaningfully by various learning styles, promoting flexibility in learning as one can study virtually from any distance and at any time with no tensity in place and time.